2017
DOI: 10.1101/141192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multisite generalizability of schizophrenia diagnosis classification based on functional brain connectivity

Abstract: Our objective was to assess the generalizability, across sites and cognitive contexts, of schizophrenia classification based on functional brain connectivity. We tested different training-test scenarios combining fMRI data from 191 schizophrenia patients and 191 matched healthy controls obtained at 6 scanning sites and under different task conditions. Diagnosis classification accuracy generalized well to a novel site and cognitive context provided data from multiple sites were used for classifier training. By … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Again, we obtained low average accuracies (with means in the range 0.51 -0.66), reinforcing the evidence for disease heterogeneity. Interestingly, these results are consistent with a recent study [Orban et al, 2017] on multisite generalizability of schizophrenia diagnosis based on functional brain connectivity, which reported multisite classification accuracies below 70%, in contrast to over 30 previously published, largely single-site schizophrenia studies, whose average reported classification accuracy exceeds 80%.…”
Section: Discussionsupporting
confidence: 91%
“…Again, we obtained low average accuracies (with means in the range 0.51 -0.66), reinforcing the evidence for disease heterogeneity. Interestingly, these results are consistent with a recent study [Orban et al, 2017] on multisite generalizability of schizophrenia diagnosis based on functional brain connectivity, which reported multisite classification accuracies below 70%, in contrast to over 30 previously published, largely single-site schizophrenia studies, whose average reported classification accuracy exceeds 80%.…”
Section: Discussionsupporting
confidence: 91%
“…The debate about the complex composition of global signals and the necessity of GSR in data preprocessing and data analysis always exists in most cases [24,54,55]. Some studies reported that the global signal was likely to reflect important neuronal components in rs-fMRI data [17,18,39]. Qing et al [26] reported that GSR effects are region-specific and suggested that it is great to report results both with and without GSR in ReHo study.…”
Section: Disease Markersmentioning
confidence: 99%
“…An increasing number of studies have reported that multimodal brain data can improve diagnostic accuracy by combining the information obtained from different MRI imaging modalities [8,[14][15][16]. The machine learning (ML) technique is a new approach that can extract relevant information from images and construct models to determine the probability of disease onset, and it can make a higher accurate prediction compared with conventional methods [5,6,13,17,18]. Salvador et al [15] achieved 75.76% accuracy in schizophrenia diagnosis, and de Filippis et al [5] reported that support vector machine associated with other ML techniques could achieve accuracy close to 100%.…”
Section: Introductionmentioning
confidence: 99%
“…Bigger data sets are needed to avoid overfitting and to build a classifier with better generalizability. Second, only one modality of data (rsfMRI) was utilized, even though both functional and structural brain information may be important for high-accuracy classification using machine learning (Mikolas et al, 2017;Orban et al, 2018;Ota et al, 2012). Third, we did not collect the smoking status of our participants in this study.…”
Section: Limitationmentioning
confidence: 99%